Optical Fibers Based on Modified Silver Halide Crystals for Nuclear Power - Salimgareev, D D; Lvov, A E; Korsakova, E A; Korsakov, A S; Zhukova, L V (KnE Materials Science, 2018)
We investigated the possibility of the deployment of AgBr – TlBr0.46I0.54MIR fibers in high ionizing radiation environment. For this purpose, we exposed plate samples made of AgBr – TlBr0.46I0.54crystals to β-ionizing radiation at a dose of 100 kGy. We revealed the radiation-induced translucence effect for these materials and assumed its nature. As the investigation showed the suitability of the fibers for the application in high ionizing radiation environment, the authors propose to use these fibers jointly with FTIR spectrometers for the online monitoring of various chemical processes at the nuclear power plants. Keywords: modified silver halides, MIR fibers, FTIR spectroscopy, ionizing radiation resistance